Influence of Cooling Rate in High-Temperature Area on Hardening of Deposited High-Cutting Chrome-Tungsten Metal; IOP Conference Series: Materials Science and Engineering; Vol. 91: VI International Scientific Practical Conference on Innovative Technologies and Economics in Engineering, Yurga, Russia, 21-23 May 2015 - Malushin N. N.; Valuev D. V. Denis Viktorovich; Valueva A. V. Anna Vladimirovna; Serikbol A.; Borovikov I. F. (Innovative technologies for producing and machining materials in mechanical engineering, 2015)
Title screen